2020
DOI: 10.1016/j.biocontrol.2020.104356
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risks of non-target feeding by the accidentally introduced ragweed leaf beetle, Ophraella communa, to native European plant species

Abstract: In 2013, the North American oligophagous leaf beetle, Ophraella communa LeSage (Coleoptera: Chrysomelidae), was found in Europe for the first time. Recent studies in Northern Italy and Southern Switzerland record extensive defoliation by O. communa on its preferred host, common ragweed, Ambrosia artemisiifolia L. (Asteraceae, Tribe Heliantheae), and reductions in its flowering and seeding. In some regions in Northern Italy, this has reportedly led to a > 80% depletion in airborne A. artemisiifolia pollen conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…An important herbivore antagonist of Ambrosia is Ophraella communa , an oligophagous leaf beetle native to North America that prefers Ambrosia as its host plant (Augustinus, Gentili, et al, 2020; Futuyma et al, 1995) (Figure 1b). Following its accidental introductions, it is currently the most successful biocontrol agent against Ambrosia in China (Ma et al, 2008; Zhou et al, 2011) and also causes considerable damage to Ambrosia in Japan (Fukano & Doi, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important herbivore antagonist of Ambrosia is Ophraella communa , an oligophagous leaf beetle native to North America that prefers Ambrosia as its host plant (Augustinus, Gentili, et al, 2020; Futuyma et al, 1995) (Figure 1b). Following its accidental introductions, it is currently the most successful biocontrol agent against Ambrosia in China (Ma et al, 2008; Zhou et al, 2011) and also causes considerable damage to Ambrosia in Japan (Fukano & Doi, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Ambrosia produces a range of chemical compounds that contribute to herbivore resistance (van Boheemen, Bou-Assi, et al, 2019), including sesquiterpene lactones (Taglialatela-Scafati et al, 2012). An important herbivore antagonist of Ambrosia is Ophraella communa, an oligophagous leaf beetle native to North America that prefers Ambrosia as its host plant (Augustinus, Gentili, et al, 2020;Futuyma et al, 1995) (Figure 1b). Following its accidental introductions, it is currently the most successful biocontrol agent against Ambrosia in China (Ma et al, 2008;Zhou et al, 2011) and also causes considerable damage to Ambrosia in Japan (Fukano & Doi, 2013) Zhou et al, 2014), which allows it to build up high local densities during the second half of the Ambrosia growing season, leading to complete defoliation and death of Ambrosia (Müller-Schärer et al, 2018;Zhou et al, 2014).…”
Section: At Er I a L S A N D M Et Hod Smentioning
confidence: 99%
“…Ophraella communa females and males can fly 25.4 and 21.4 km in 23 h, respectively, indicating a high dispersal rate (Tanaka & Yamaka, 2009). Studies have shown that O. communa can reduce the amount of aerial pollen of A. artemisiifolia by up to 80% (Augustinus et al, 2020). In the coming years it is expected that concentration of aerial pollen will be reduced in the area where O. communa has established in Bosnia and Herzegovina and this will decrease the negative health impact on the population (Bonini et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Further, larval survival on sunflower is low and newly emerged adults leave the sunflower to look for A. artemisiifolia plants in most cases. Besides, there is no European direct proof in connection with the non‐target effects of this herbivore (Augustinus, Gentili, et al, 2020). In our opinion as well, its deploying on the new habitats as a biological control agent can be a low risk.…”
Section: Discussionmentioning
confidence: 99%
“…Ophraella communa has a narrow host range, damaging mainly plants of the Asteraceae family. It may be a cause of concern that it damages not only weeds ( A. artemisiifolia, Iva xanthiiifolia, Artemisia vulgaris, Xanthium spp., Conyza canadensis, Inula graveolens, Persicaria maculosa ) but also crop plants ( Helianthus annuus, H. tuberosus ), although food choice tests under laboratory conditions proved that O. communa prefers A. artemisiifolia to other hosts (Augustinus, Gentili, et al, 2020; Dernovici et al, 2006; Palmer & Goeden, 1991; Tóth et al, 2014). The larvae and the adults of the beetle feed on A. artemisiifolia leaves, and in case of strong infestation, they can entirely destroy ragweed populations before flowering or considerably reduce seed and pollen production (Bonini et al, 2015; Palmer & Goeden, 1991; Wan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%